2008
DOI: 10.1002/clen.200700074
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Recovery from Human Urine Using Pretreated Zeolite and Struvite Precipitation in Combination with Freezing‐Thawing and Plant Availability Tests on Common Wheat

Abstract: The nutrient rich fractions in wastewater originating from human urine and can be recovered as solids for more efficient recycling, facilitated handling and storage for reuse in agriculture. Freezing and thawing can be used to concentrate the urine nutrients. Phosphorus (P) and nitrogen (N) can be precipitated as struvite [(Mg,Ca)(K,NH 4 )(PO 4 ) N 6H 2 O] by adding MgO and additional nitrogen can be recovered by using zeolites. The zeolite in this study was pretreated in two ways: (i) washed and (ii) washed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Nutrient-enriched clinoptilolite resulted in up to a fourfold and sixfold increase in yield and N uptake, respectively. These findings were in line with studies that report N-loaded zeolite to be a good source of N (Ganrot et al, 2008) and urine-enriched clinoptilolite to be as effective as chemical fertilizer in preliminary pot trials (Beler-Baykal et al, 2011;Kocatü rk and Baykal, 2012).…”
Section: Effects Of Enriched Sorbents On Plant Growth and N Uptakesupporting
confidence: 91%
“…Nutrient-enriched clinoptilolite resulted in up to a fourfold and sixfold increase in yield and N uptake, respectively. These findings were in line with studies that report N-loaded zeolite to be a good source of N (Ganrot et al, 2008) and urine-enriched clinoptilolite to be as effective as chemical fertilizer in preliminary pot trials (Beler-Baykal et al, 2011;Kocatü rk and Baykal, 2012).…”
Section: Effects Of Enriched Sorbents On Plant Growth and N Uptakesupporting
confidence: 91%
“…This clearly showed that N from nutrient-enriched clinoptilolite was available to the grass. These findings were in line with studies that report nitrogenloaded zeolite to be a good source of N (Ganrot et al, 2008) and urineenrichedclinoptilolite to be as effective as chemical fertiliser in preliminary pot trials (Beler-Baykal et al, 2011;. Many researchers have reported a high retention of nitrogen on the surface of biochar, even when using KCl extraction for desorption, which should replace NH4 + ions with K + and result in high desorption ratios.…”
Section: Discussionsupporting
confidence: 88%
“…Clinoptilolite has been found to be efficient at removing orthophosphate from aqueous solutions (Milan et al, 1997;Ganrot et al, 2007;Allar & Beler-Baykal, 2013;Lin et al, 2015), even though orthophosphate is an anion and cannot be removed through ion exchange by clinoptilolite. Orthophosphate removal occurs via physical adsorption on Al 3+ sites of clinoptilolite (Sakadevan & Bavor, 1998;Ganrot et al, 2008).…”
Section: Clinoptilolite As a Sorbentmentioning
confidence: 99%
See 2 more Smart Citations